Ameliorative effect of membrane-associated estrogen receptor G protein coupled receptor 30 activation on object recognition memory in mouse models of Alzheimer's disease - Takashi Kubota; Hiroshi Matsumoto; Yutaka Kirino (Elsevier, 2016)
Membrane-associated estrogen receptor "G protein-coupled receptor 30" (GPR30) has been implicated in spatial recognition memory and protection against neuronal death. The present study investigated the role of GPR30 in object recognition memory in an Alzheimer's disease (AD) mouse model (5XFAD) by using novel object recognition (NOR) test. Impairment of long-term (24 h) recognition memory was observed in both male and female 5XFAD mice. Selective GPR30 agonist, G-1, ameliorated this impairment in female 5XFAD mice, but not in male mice. Our study demonstrated the ameliorative role of GPR30 in NOR memory impaired by AD pathology in female mice.